Plug-in battery electric vehicle : design and fabrication of transition structure for marriage of shell to chassis - Lim, Jia Hong (2018)
The Nanyang Venture 7 (NV7), NTU Plug-in Battery Electric Vehicle (BEV) started as an initiative for students to design and fabricate an electric vehicle that utilises a clean source of energy, mainly electrical energy stored in the rechargeable lithium ion battery packs to power the vehicle. The BEV rans on electric motor instead of the conventional cars which runs petrol and an internal combustion engine. Over the years, past students have worked on & constructed the chassis of the vehicle. Collaboration with the School of Art Design & Media (NTU) has also bring forth the design and fabrication of the external shell of the BEV. In this project, the author was tasked to design and fabricate transitional methods or structures to allow the marriage of the external shell to the high alloy steel chassis. As the external shell is flimsy and malleable, the structure had to be able to hold the external shell in place whist ensuring that it is rigid and strong. Before the design process, multiple areas of studies were carried out which include, traditional car manufacturing methods & different types of manufacturing methods available to the author which include sheet metal bending, cutting, grinding, welding and 3D printing. After which the ideal methods are identified and designing of the structure proceeded. The structural design considered the forces the structure might encounter with simulation and calculation to ensure that the designed structure would be able to meet the requirements. After ensuring the design is suitable, the structure is then fabricated and installed. The external shell is then secured onto the structure, completing the project